SELF-ACTUALIZATION OF THE MAIN CHARACTER, NOAH CALHOUN IN THE NOTBOOK NOVEL - Jaya, Ferry Fitra; Arifin, M. Bahri; Lubis, Indah Sari (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
Self-actualization is the highest level of psychological development that motives all human behaviors towards the full realization of a person’s higher potential life. This study aims at revealing Noah Calhoun as the main character of his self-actualization in The Notebook novel. The idea of self-actualization itself will be elaborated by using Maslow’s Hierarchy of Needs. Moreover, this study is conducted by using qualitative method. The researcher generated the data from every chapter of the book, including dialogue, words, phrases, sentences which deal with self-actualization’s character. In dealing with the researcher’s purpose, it was found that Noah Calhoun has attained his physiological needs, safety and security needs, love and belonging needs, and esteem needs sufficiently and also the characteristics of self-actualized person. It can be seen in what Noah Calhoun did on the situation described in the novel.